Foreign Aid Effectiveness and Global Partnerships: Implications for Nigeria's National Development - Jingi, Auwal Alhaji; Gusau, Sani Abdullahi; Aliyu, Abba Nuru (Kashere Journal of Politics and International Relations, 2025)
Foreign aid has been a crucial factor in Nigeria's development, impacting economic growth, infrastructure, healthcare, and education. However, its effectiveness is often debated due to issues such as corruption, mismanagement, donor-imposed conditions, and aid dependency. This study examines the effectiveness of foreign aid in Nigeria and the influence of global partnerships on national development. Employing a conceptual framework, the research analyses various aid models, including bilateral and multilateral assistance, humanitarian aid, and technical support. Key findings highlight the relevance of theoretical perspectives like Dependency Theory, showing that foreign aid can either promote economic growth or entrench reliance on external support. A comparative analysis with Ghana and Rwanda emphasizes the significance of governance, policy alignment, and strategic aid utilization. While foreign aid has significantly contributed to Nigeria’s development, its potential remains unfulfilled due to structural inefficiencies and inadequate policy implementation. The study recommends enhancing transparency and anti-corruption measures, aligning aid with national priorities, reducing dependency through local revenue generation, and reforming donor conditionality’s. Furthermore, fostering regional partnerships and investing in sustainable initiatives will improve aid effectiveness. By addressing these challenges, Nigeria can move towards economic self-sufficiency while ensuring that foreign aid effectively supports national development